Speaking Medicine in the Silent Language: Experience with a Deaf Patient in Sri Lanka - Jayawardana, Hettiarachchige D. P. (International Journal of Medical Students, 2021)
Being deaf can pose challenges in everyday living, due to the fact that most deaf people cannot effectively communicate with the majority of non-deaf people in society. Effective communication plays a vital role when seeking medical services. As a developing nation, there have been several steps taken in Sri Lanka to bridge the communication gap between deaf and non-deaf people. Nevertheless, there is still a need to introduce a cost-effective communication system in governmental healthcare services. This experience highlights the importance of bridging the gap between healthcare providers and deaf patients, and suggests possible cost-effective ways to provide better quality healthcare services.